Individual differences in frontoparietal plasticity in humans - Boroshok, Austin L.; Park, Anne T.; Fotiadis, Panagiotis; Velasquez, Gerardo H.; Tooley, Ursula A.; Simon, Katrina R.; Forde, Jasmine C. P.; Delgado Reyes, Lourdes M.; Tisdall, M. Dylan; Bassett, Dani S.; Cooper, Emily A.; Mackey, Allyson P. (NPJ science of learning, 2022)
Neuroplasticity, defined as the brain’s potential to change in response to its environment, has been extensively studied at the cellular and molecular levels. Work in animal models suggests that stimulation to the ventral tegmental area (VTA) enhances plasticity, and that myelination constrains plasticity. Little is known, however, about whether proxy measures of these properties in the human brain are associated with learning. Here, we investigated the plasticity of the frontoparietal system by asking whether VTA resting-state functional connectivity and myelin map values (T1w/T2w ratios) predicted learning after short-term training on the adaptive n -back ( n = 46, ages 18–25). We found that stronger baseline connectivity between VTA and lateral prefrontal cortex predicted greater improvements in accuracy. Lower myelin map values predicted improvements in response times, but not accuracy. Our findings suggest that proxy markers of neural plasticity can predict learning in humans.